Epilepsy: recognition and management of seizures in children and young people. (2nd June 2021) - Pickering, Christopher
Abstract : A seizure describes the signs and symptoms associated with a sudden surge in brain activity. It is a symptom of either acute brain disturbance, or may indicate a diagnosis of epilepsy, which describes an underlying tendency to have seizures. There are many different seizure types, which account for the wide variation in seizure symptoms. The principles of management remain constant for all seizure types: maintain child safety, ABC support, and arrange emergency assistance and hospital transfer for prolonged episodes. In addition to this, tonic-clonic seizures lasting for more than 5 minutes require treatment with benzodiazepines. Buccal midazolam or rectal diazepam are first-line options when intravenous or intraosseous access is not available. Children and young people with epilepsy should have individualised treatment plans which, if available, further simplify emergency treatment decisions.